The Role of Digital Forensics in Cybercrime on Twitter Social Media - Azzahra, Rahma; Rachma Dina, Intan (SAINTEKBU, 2024)
The rapid advancements in information technology in the current era have significant positive and negative effects. One notable benefit of these developments is the ease with which individuals can access information and communicate with others through social media platforms. However, a major drawback is the irresponsible behavior exhibited by some users, leading to an increase in cybercrime. Twitter, in particular, is frequently targeted for such criminal activities. Digital forensics, a specialized branch of forensic science, focuses on the identification and recovery of data, particularly related to computer crimes. This initiative aims to highlight the risks of cybercrime associated with social media platforms like Twitter. The research conducted seeks to gather digital evidence by utilizing one specific method endorsed by the National Institute of Justice (NIJ), which encompasses the following stages: Collection, Examination, Analysis, and Reporting.